2000
DOI: 10.1086/316888
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Scan in Families from Australia and New Zealand Confirms the Presence of a Maternal Susceptibility Locus for Pre-Eclampsia, on Chromosome 2

Abstract: Epidemiological studies have shown that genetic factors contribute to the etiology of the common and serious pregnancy-specific disorder pre-eclampsia (PE)/eclampsia (E). Candidate-gene studies have provided evidence (albeit controversial) of linkage to several genes, including angiotensinogen on 1q42-43 and eNOS on 7q36. A recent medium-density genome scan in Icelandic families identified significant linkage to D2S286 (at 94.05 cM) on chromosome 2p12 and suggestive linkage to D2S321 (at 157.5 cM) on chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
129
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 37 publications
0
129
0
4
Order By: Relevance
“…Linked loci have been found on chromosomes 2 (2p13 (15,16) and 10 (10q22q22 (17)) but to date no specific genes in the linked loci have been implicated in causing the problem. However, changes in the expression of several genes in the placenta have been proposed to affect the development of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Linked loci have been found on chromosomes 2 (2p13 (15,16) and 10 (10q22q22 (17)) but to date no specific genes in the linked loci have been implicated in causing the problem. However, changes in the expression of several genes in the placenta have been proposed to affect the development of PE.…”
Section: Introductionmentioning
confidence: 99%
“…23 Evidence for a preeclampsia locus on chromosome 2 was confirmed by a similar genome-wide scan in 34 families from Australia and New Zealand from Moses et al who found suggestive evidence of linkage to chromosome 2q at 144.7 cM. 24 The current Dutch genome-wide scan was performed at the same laboratory as and in close collaboration with Arngrõ Âmsson and coworkers; 265 individuals from 67 Dutch families were genotyped at 293 microsatellite markers.…”
Section: Introductionmentioning
confidence: 73%
“…We re-analysed our data for families with only preeclampsia cases (preeclampsia families; n=38) and families with at least one sibling with HELLP-syndrome (HELLP families; n=34) separately, since in the previous scans 22,24 no HELLPsyndrome cases had been recruited. Figure 1 Results genome-wide scan in 67 Dutch families.…”
Section: European Journal Of Human Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al reevaluar las familias con HELLP, se encontró un LOD score en el cromosoma 12q que incrementó en las familias con HELLP y casi desapareció en las familias que no tenían el síndrome. Otro valor observado en un marcador en el cromosoma 11, en las familias con preeclampsia se traslapó con el segundo valor más alto en el estudio australiano (116). A pesar de la diversidad de resultados encontrados en este estudio en comparación con los estudios previos, los autores concluyeron que según este barrido genómico el síndrome HELLP podría tener una base genética diferente a la de la preeclampsia sin HELLP.…”
unclassified